Nurses' Attitudes toward Research Utilization in Clinical Practice - Mehrdad N; Salsali M; Kazemnejad A (Tehran University of Medical Sciences, 2007)
Background & Objective: Research utilization is a new phenomenon in Iran and the Iranian nurses tend to practice based on evidences. The objective of this research is to investigate nurses' attitude toward research utilization.Methods & Materials: This research is an analytical-descriptive study. The sample included 410 clinical nurses and instructors who were selected through multistage stratified sampling method. Data were gathered using a two-section questionnaire and analyzed using statistical package for social sciences (SPSS).Results: 91.2% of respondents believed in using research findings in practice. 77.6% of nurses agreed with the following statement: "Research is not applicable in practice". Furthermore 88.3% agreed that" Research helps to build a scientific base for nursing". The majority of respondents had positive attitude toward research utilization. There was a significant difference between attitude and kind of professional activity, setting and research activity. Conclusion: It seems having positive attitude toward research utilization is not sufficient for applying research results in practice. In order to utilize the research findings, more relevant research in this field of nursing is required.